Efektivitas Penegakan Hukum Pertahanan Negara Pada Sektor Maritim Indonesia - Abdil Azizul Furqon; Irwan Triadi (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
This article focuses on the effectiveness of law enforcement in the maritime sector. This is very important, considering that Indonesia is one of the countries with the longest coastal latitude in the world. So it is important to discuss this issue. Regarding the research method used is descriptive qualitative using data collection methods, namely library research. Based on the author's analysis, it can be concluded that law enforcement practices in the Indonesian maritime sector still have several shortcomings. Based on the author's analysis, state defense law enforcement practices in the Indonesian maritime sector are still not effective. This is due to overlapping laws and regulations in Indonesia. The impact of this overlap results in the spread of law enforcement agencies and difficulties in providing facilities and infrastructure for law enforcement in Indonesian waters. These conditions mean that Indonesia's national defense in the maritime region often experiences violations of the law, both by the Indonesian people and other countries, both by individuals and groups.